MAKING VISIBLE THE INVISIBLE HAND OF NEOLIBERAL THOUGHT IN COSTA RICA: BIRTH AND TRAJECTORY OF THE NATIONAL ASSOCIATION OF ECONOMIC DEVELOPMENT (ANFE): 1958-1975 - Marchena Sanabria, Jorge (2011)
The following article deals with Costa Rican intellectual and political history, particularly focusedon the National Association of Economic Development (AsociaciónNacional de FomentoEconómico-ANFE).This organization was created in 1958 with the purpose of studying and transforming the Costa Rican State in the second half of the twentieth century and proposing policies aimed at developing the economy, making it more consistent with the free-market and reduction of state interventionliberal models.The article is part of a more extensive investigation, for which a wider corpus of documents was analyzed than the one cited here.